2023
DOI: 10.3390/ma16062167
|View full text |Cite
|
Sign up to set email alerts
|

Ageing Evaluation of Foamed Polymer Modified Bitumen with Bio-Flux Additive

Abstract: This paper presents the results of an analysis of the changes in the stiffness of asphalt binders modified with a bio-flux additive and subjected to the processes of foaming and short-term ageing. The purpose of the analyses was to determine changes in the rheological properties of asphalt binder as a result of technological processes characteristic of hot and warm mix asphalt technology. Three asphalt binders with similar penetration but varying degrees of polymer modification were tested: 50/70, 45/80–55 pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Therefore, a number of studies have been conducted to evaluate the effects of aging temperature on the properties of WMA asphalt binders. The observations made in the field sections were confirmed in laboratory studies [8][9][10][11][12][13][14], showing a great dependence of the high-temperature properties of the asphalt binders on the laboratory aging protocols and the aging temperatures in particular. In studies comparing asphalt binders recovered from asphalt mixtures and the RTFOT-aged binders [15][16][17], it was shown that the standard temperature during short-term aging (163 • C) was too high to reflect the aging processes during the production of WMA mixtures, while 123 • C can be considered too low.…”
Section: Introductionsupporting
confidence: 60%
“…Therefore, a number of studies have been conducted to evaluate the effects of aging temperature on the properties of WMA asphalt binders. The observations made in the field sections were confirmed in laboratory studies [8][9][10][11][12][13][14], showing a great dependence of the high-temperature properties of the asphalt binders on the laboratory aging protocols and the aging temperatures in particular. In studies comparing asphalt binders recovered from asphalt mixtures and the RTFOT-aged binders [15][16][17], it was shown that the standard temperature during short-term aging (163 • C) was too high to reflect the aging processes during the production of WMA mixtures, while 123 • C can be considered too low.…”
Section: Introductionsupporting
confidence: 60%